Revealing the interplay between decarbonisation, circularity, and cost-effectiveness in building energy renovation - Chunbo Zhang; Mingming Hu; Benjamin Sprecher; Romain Sacchi; Xining Yang; Shiyu Yang; Teun Johannes Verhagen; Chi Zhang; Bernhard Steubing; Arnold Tukker (Nature Communications)
Abstract Building energy renovation mitigates carbon emissions but often increases material demand and financial costs. This work addresses this problem by investigating the carbon, material, and economic footprints of various renovation scenarios in the Dutch residential sector from 2015 to 2050. Results show that, compared to the baseline, façade refurbishment could lower cumulative lifecycle emissions by up to 0.3%, while raising material use by 21–25% and costs by 2–6%. Sensitivity analysis indicates that refurbishing the heating system offers greater potential for reducing carbon emissions. Rebuilding could cut emissions by up to 17% under an ambitious energy transition, though this would triple material use and construction costs. Circularity strategies could offset up to 89% of the material footprint and reduce carbon emissions by up to 23%. Nonetheless, considerable cost increases from renovations remain inevitable, even with advanced material circulation systems, suggesting circular renovation strategies with enhanced incentives as concerted action.